"Only in theaters" in an on-demand culture: Event movies as media events. (2nd October 2022) - Moulton, Carter
ABSTRACT: What is so eventful about an event movie's arrival to the multiplex, and how does this eventfulness function as both an industry strategy and audience experience? Synthesizing an analysis of trade discourses, promotional campaigns, and manually-curated box office data, this article considers how the concept of eventfulness emerged as a discursive construction and spatiotemporal formation used by the industry to promote moviegoing as more meaningful than other forms of media experience in today's "anywhere-anytime" and "on-demand" culture. Eventfulness situates the movie theater at the center of a specific, layered structure of time – a stretched sense of promotional anticipation and cultural nostalgia which climaxes during an ephemeral moment – and space – a discursive space of cultural buzz leading up to the event, a local experience community marked by fan participation, and an imagined global audience which takes shape through the synchronization of the event as it simulates "live" broadcasting and connects audiences in time.